STUDI KOMPARASI ADSORPSI TIGA JENIS ZAT WARNA REMAZOL PADA PERMUKAAN KARBON AKTIF - Ni Luh Putu Ananda Saraswati; I Made Oka Riawan; Astrid Alvania Rihi (UIN AR-RANIRY, 2022)
Remazol is a reactive dye that is widely used in the textile industry with functional groups that can be well covalently bonded to textile fibres, but difficult to decompose, carcinogenic, and harmful to the health and ecosystems. This study specifically aims to analyse the adsorption power of activated carbon on three types of Remazol dyes using batch experiment method as an effective way to reduce the concentration of these dyes in textile industry wastewater. Using activated carbon with the same treatment, Remazol Red dye had the best interaction and was adsorbed in the highest amount on the activated carbon surface (125.16 mg/g), followed by Remazol Blue (16.23 mg/g) and finally Remazol Black dye (11.07 mg/g). The three adsorption processes that occur are in accordance with the Langmuir adsorption isotherm model, with color removal percentage of 74.4 % (Remazol Red), 49.5 % (Remazol Blue), and 48.1 % (Remazol Black). These results are in accordance with the structural studies conducted on the three types of Remazol synthetic dyes, in which Remazol Black with the bulkiest structure has the weakest physical interaction with carbon atoms on the activated carbon surface thus absorbed in the least amount on the adsorbent surface.